2020
DOI: 10.1248/bpb.b19-00495
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Limonene (+) against Aβ42-Induced Neurotoxicity in a <i>Drosophila</i> Model of Alzheimer’s Disease

Abstract: Forest bathing is suggested to have beneficial effects on various aspects of human health. Terpenes, isoprene based-phytochemicals emitted from trees, are largely responsible for these beneficial effects of forest bathing. Although the therapeutic effects of terpenes on various diseases have been revealed, their effects on neuronal health have not yet been studied in detail. Here, we screened 16 terpenes that are the main components of Korean forests using Drosophila Alzheimer's disease (AD) models to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…On the other hand, several studies have shown the effects of terpenes on the production of pro-inflammatory mediators during neuroinflammation in in vivo models. For example, d-limonene decreased NO levels in Aβ42-expressing fly heads [48], and linalool reduced the levels of the pro-inflammatory markers p38 MAPK, NOS2, COX2 and IL-1β in the brain of a triple transgenic mouse model of Alzheimer's disease (3xTg-AD) [73]. Moreover, borneol attenuated the elevation of NO, the increase in iNOS enzymatic activity and the upregulation of iNOS expression in an ischemic model of oxygen-glucose deprivation followed by reperfusion [65].…”
Section: Regulation Of Pro-inflammatory Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several studies have shown the effects of terpenes on the production of pro-inflammatory mediators during neuroinflammation in in vivo models. For example, d-limonene decreased NO levels in Aβ42-expressing fly heads [48], and linalool reduced the levels of the pro-inflammatory markers p38 MAPK, NOS2, COX2 and IL-1β in the brain of a triple transgenic mouse model of Alzheimer's disease (3xTg-AD) [73]. Moreover, borneol attenuated the elevation of NO, the increase in iNOS enzymatic activity and the upregulation of iNOS expression in an ischemic model of oxygen-glucose deprivation followed by reperfusion [65].…”
Section: Regulation Of Pro-inflammatory Mediatorsmentioning
confidence: 99%
“…TNF-α, IL-1β and IL-6 ↓ LPS-stimulation Raw 264.7 cell line [46] NF-kB, COX-2, iNOS and Nitrite levels ↓ Doxorubicin-induced inflammation Wistar rats [47] NO levels ↓ Aβ42 expressed heads Fruit fly [48] NO and iNOS levels ↓ In vitro treatment Human chondrocytes [49] Myrcene NO and iNOS levels ↓ In vitro treatment Human chondrocytes [49] γ-Terpinene TNF-α and IL-1β ↓ Carrageenan-induced peritonitis model Swiss mice [50] IL-1β, IL-6↓ and IL-10, COX-2, PGE2 ↑ LPS-Stimulation Macrophages from mice [51] α-Phellandrene TNF-α and IL-6 ↓ Carrageenan injection in air pouch cavities Wistar rats or swiss mice [52] IL ↓ denotes decreased activity; ↑ denotes increased activity.…”
Section: Pro-inflammatory Mediator D-limonenementioning
confidence: 99%
See 1 more Smart Citation
“…D-limonene metabolites have been detected in adipose tissue and mammary glands in a high concentration, although it has low toxicity [101]. This compound shows different pharmacological properties, which include anti-inflammatory, gastro-protective, anti-nociceptive, anti-tumor, and neuroprotective [102][103][104]. A recent study has demonstrated D-limonene anti-tumor activity (i.e., tumor cells decreased in proliferation and growth) in an animal model of chronic myeloid leukemia [102].…”
Section: D-limonenementioning
confidence: 99%
“…At a different point-of-view, Smeriglio and colleagues reported the antioxidant and free radical scavenging properties of Citrus lumia oil, which is highly-concentrated in monoterpenes (e.g., 48.9% D-limonene and 18.2% linalool), suggesting an important preventive role in the genesis of oxidative stress-related pathologies [111]. In this context, a study conducted by Shin et al showed that limonene decreased cell death, ROS levels, extracellular signal-regulated kinase phosphorylation, and overall inflammation in the brains and eyes of drosophila during Aβ42-induced neurotoxicity, a model of Alzheimer's disease (AD) [104]. These and other authors have been studying limonene effects in the context of its impacts in the CNS.…”
Section: D-limonenementioning
confidence: 99%